Bank competition and corporate employment: Evidence from the geographic distribution of bank branches in China - Lai, Shaojie; Chen, Lihan; Wang, Qing Sophie; Anderson, Hamish D. (Journal of Banking & Finance, 2023)
Using the geographic location data of 218,554 commercial bank branches in China, we find that an increasing number of bank branches in the vicinity of enterprises, namely bank competition, leads to higher corporate employment, particularly for non-SOEs and SOEs with less government influence. Channel analyses reveal that better access to banking facilitates information extraction and eases credit constraints for surrounding firms, which thus increases labor investment. In addition, fintech development moderates the positive effect of bank competition on corporate employment. An exogenous policy shock as well as two instrumental variables, are used to correct for endogeneity and our results remain consistent. The findings are also robust to alternative samples, proxies, and different fixed effects. Further analyses show that bank competition improves firms’ labor investment efficiency and upgrades their employment structures. Lastly, increased employment improves the firm performance of non-SOEs.